2013
DOI: 10.1063/2.1306202
|View full text |Cite
|
Sign up to set email alerts
|

A novel MAV with treadmill motion of wing

Abstract: The Magnus effect is well known phenomena for producing high lift values from spinning symmetrical geometries such as cylinders, spheres, or disks. But, the Magnus force may also be produced by treadmill motion of aerodynamic bodies. To accomplish this, the skin of aerodynamic bodies may circulate with a constant circumferential speed. Here, a novel wing with treadmill motion of skin is introduced which may generate lift at zero air speeds. The new wing may lead to micro aerial vehicle configurations for verti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…5); but, no computational or experimental studies was found in literature to address this. Samani and Sedaghat [8] have examined the application of such an aerofoil in a novel vertical take-off Micro Air Vehicle (MAV). To our knowledge, some computational or experimental efforts were made towards analysis and simulation of spinning cylinders in the leading or trailing edges of aerofoil such as shown in (Fig.…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…5); but, no computational or experimental studies was found in literature to address this. Samani and Sedaghat [8] have examined the application of such an aerofoil in a novel vertical take-off Micro Air Vehicle (MAV). To our knowledge, some computational or experimental efforts were made towards analysis and simulation of spinning cylinders in the leading or trailing edges of aerofoil such as shown in (Fig.…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…In cases where fluid velocity on the surface varies during time intervals, it is not recommended to use these covers. 79 Because of the positive pressure gradient created on the surface, the vortex is aroused in the back surface as flow passing over the surface. But, as shown in Figure 1, riblets steer the flow and delay the separation, which causes reduction in the total drag.…”
Section: Introductionmentioning
confidence: 99%